PENGARUH PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK (Project Based Learning) TERHADAP KECAKAPAN KOMUNIKASI SISWA PADA KONSEP BIODIVERSITAS - Iing Dwi Lestari; Suroso Mukti Leksono; Siti Romlah Noer Hodijah; Wulan Agustina (FPMIPA IKIP PGRI Bali, 2016)
This study aimed to determine the effect of projectbased learning model to the communication skills of students on the concept of biodiversity. The method used is a quasi-experimental design with randomized control group only. This research was conducted at SMA Negeri 5 Kota Serang class X academic year 2011/2012. The sampling technique used in this research were cluster random sampling. Data retrieval research using the assessment presentations and reports. Results of the research is the average value of communication skills of students in the experimental class is 68.4% (good) and the control class is 45.8% (approximately). Based on t-test obtained tcount (8.545) ≥ ttable (2,002) or significance 0.002> 0.05. It can be concluded that there is significant implementation project based learning model on the concept of biodiversity to the communication skills of students of SMAN 5 Serang.